Application of STEM-Integrated Cognitive Conflict-based Augmented Reality to Student Self-Efficacy to Achieve 21st Century Learning Success - Abdilah, Zuhdi; Mufit, Fatni; Hidayati, Hidayati; Riyasni, Selma (PILLAR OF PHYSICS EDUCATION, 2025)
This study aims to examine the effectiveness of Augmented Reality (AR) teaching materials based on cognitive conflict integrated with the STEM approach to increase student self-efficacy in the material of Newton's law of gravity. The research used a quasi-experimental design with a non-equivalent control group design model involving 72 SMA / MA students divided into experimental and control groups. The main instrument was a student self-efficacy questionnaire. The results showed that the use of STEM-integrated cognitive conflict-based AR significantly increased students’ self-efficacy compared to conventional learning. The average self-efficacy score of the experimental group is higher, with an increase that falls into the moderate category. This finding indicates that the integration of technology and cognitive conflict strategies in the STEM approach can be an effective, innovative learning alternative to build students' self-efficacy in understanding physics concepts.